Organizational Culture and Job Satisfaction: A Case of Academic Staffs at Universiti Utara Malaysia (UUM) - Bashayreh, Anas Mahmoud Khaled (2009)
The main purpose of this study is to examine and gain a better understanding of the significant relationships between the dimensions of organizational culture and employees’ job satisfaction among academic staff at UUM. It was done among 135 lecturers at UUM. Data which was gathered through questionnaires was analyzed by using statistical package for social science (SPSS) software 12.0. Two types of statistic were used namely descriptive and inferential statistic. Frequency and percentage were the type of statistic descriptive and statistic inferential used were multiple regression and Pearson correlation. The result showed that no significant between (emphasis of reward and performance oriented) and job satisfaction. Result also showed that significant between (organizational supportiveness, innovation and stability and communication) and job satisfaction.